(untitled) (Muitas Vozes, 2021)
This article is part of a Master’s thesis research that aimed to understand the meanings of language in the imagery of common sense, in the linguistic perspective of enunciative semantics. The proposal is to analyze how the semantic functioning of (re)saying occurs in the analytical process of rewriting. The theoretical-methodological support is based on the Theory of Enunciation, in the perspective of the Semantics of the Event (GUIMARÃES, 2002b). In this way, with the enunciative operators of rewriting mentioned, the meanings of language present in the imagery of common sense are analyzed, and subsequently the recurrence of modes of rewriting and its semantic functioning. It was observed that the substitution and repetition modes are the most used, moving directions of specification, synonym and definition. The ways and meanings of rewriting allow to infer about how much the written and spoken use of language is still confused in the discourse of common sense, in which correction and the norm are attributed to the oral modality. Thus, a conflict arises between the linguistic function and the enunciative function, in which “good speech” is idealized and works as a criterion that qualifies, or not, the subject to occupy the social spaces of power and visibility, and the statements present the point of view of an imaginary language.